Introduction to Diesel Emissions 2020
DOI: 10.5772/intechopen.85248
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Emissions and Mitigations

Abstract: This chapter presents a concise treatment of diesel engine exhaust emissions and its mitigations. The working principle of the diesel engine is first given to establish the background and further to describe the influence of various parameters that affect the formation of engine exhaust emissions. The factors that influence exhaust emissions are linked to the engine design and the operating factors that promote good fuel-air mixing and combustion. These factors are air induction, fuel injection equipment, fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…169,170 Soot formation begins with the combustion and pyrolysis of fuel in the combustion chamber. Studies 171,172 reported that the soot particles form by nucleation of heavy molecular weight PAHs. Precursors originate from acetylene, its higher analogs ( C n H n ), and PAHs.…”
Section: Soot Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…169,170 Soot formation begins with the combustion and pyrolysis of fuel in the combustion chamber. Studies 171,172 reported that the soot particles form by nucleation of heavy molecular weight PAHs. Precursors originate from acetylene, its higher analogs ( C n H n ), and PAHs.…”
Section: Soot Evolutionmentioning
confidence: 99%
“…The Sulfates can constitute up to 14% of the PM mass. 172 Tiszenkel et al 200 investigated the influence of thermal intensity on H 2 S O 4 nucleation and growth in a low-temperature environment.…”
Section: Soot Evolutionmentioning
confidence: 99%